Inter-annual variability of oceanographic conditions and phytoplankton in Valparaíso Bay (~33°S), central Chile - Aparicio-Rizzo, Pilar; Masotti, Italo (Revista de Biología Marina y Oceanografía, 2019)
The inter-annual variability of oceanographic conditions and phytoplankton abundance and biomass was studied using 10 years (1986-1996) of in situ observations at a fixed station in Valparaíso Bay (~33ºS). The time series analysis revealed that strong S-SW winds drive a quasi-permanent upwelling activity that maintain the nutrients availability in the water column to fuel the phytoplankton in the bay. The most important changes in bio-oceanographic conditions were observed during 1987 El Niño event, which was characterized by higher temperatures but lower values for salinity, nitrate, and phosphate concentrations, together with a decrease of phytoplankton biomass compared to 1988 La Niña event when colder, saltier, and nutrient-rich upwelled water were observed. High Aconcagua River discharges were observed during the El Niño conditions (1987-1988 and 1993), which led to a decrease in surface salinity and a high abundance of dinoflagellates. Two periods with differences in bio-oceanographic conditions were observed; 1988-1992 showed lower temperatures but higher nutrients (nitrate), phytoplankton biomass and abundance of diatoms than 1993-1996 period. Throughout the study period, positive trends in upwelling activity was registered accompanied by a fall in phytoplankton biomass and dinoflagellate abundance. This paper provides new evidences concerning the influence of El Niño Southern Oscillation (ENSO) in phytoplankton and oceanographic conditions in the coastal upwelling off central Chile.